The comparison of life satisfaction-spritual health and psychological resilience among woman with geometric meditation versus non- meditator - kargar, Farzaneh; Davodi, Azam; NazarAghaei, Farshad (International Journal of Psychosocial Rehabilitation, 2020)
The objective of study is to evaluate Geometric Meditation (GM) on psychological variables including psychological resilience, spiritual well-being and life satisfaction between practicing and non-practicing women. In this this cross-sectional comparative study, the intervention group was a sample (n=32) of women who participated in a three- hour- weekly training meditation class in Shiraz for eight months in order to learn practical and fundamental concept of GM. The instruments were Conner-Davidson (2003), Palutzin and Ellison’s spiritual well-being (1983), and life satisfaction Diener (1985). According to the validity of the given questionnaire and its result, 32 participants were selected from both groups based on their age, education, and marital status. In order to examine the hypothesis, we used the Kolmogorov-Smirnov test, then independent T test was applied for evaluating resilience. GM programs show the evidence of resiliency increase (0.046<0.05). Using Mann-Whitney and Wilcoxon’s non-parametric test to analyze the variables of spiritual well-being and life satisfaction showed insignificant difference between them. However, intervention group compared to control group had a higher score mean in spiritual well-being and life satisfaction. In Conclusion, GM has a positive role in increasing resilience, life satisfaction and spiritual well-being, however, stronger studies are vital to be carried out.